Safety and tolerability of acetylcysteine and pirfenidone combination therapy in idiopathic pulmonary fibrosis: a randomised, double-blind, placebo-controlled, phase 2 trial - Behr, Jürgen; Bendstrup, Elisabeth; Crestani, Bruno; Günther, Andreas; Olschewski, Horst; Sköld, C Magnus; Wells, Athol; Wuyts, Wim; Koschel, Dirk; Kreuter, Michael; Wallaert, Benoît; Lin, Chin-Yu; et al. (The lancet. Respiratory medicine, 2016)
Background - Oral acetylcysteine (also known as N-acetylcysteine) is used with pirfenidone to treat idiopathic pulmonary fibrosis (IPF) in Europe. However, no randomised studies have investigated the safety and tolerability of this combination. The PANORAMA study assessed the safety and tolerability of acetylcysteine combined with pirfenidone in patients with IPF. Exploratory efficacy endpoints were also assessed. - Methods - We did a double-blind randomised trial at 48 sites in eight countries. Patients with IPF aged 40-80 years and established on pirfenidone (at least 1602 mg/day for 8 weeks or longer) were randomly assigned in a 1:1 ratio by interactive voice response system to receive concomitant oral acetylcysteine (600 mg, three times daily) or placebo for 24 weeks. A stratified blocked randomisation scheme was used with a block size of 4. Randomisation was stratified by dose of pirfenidone (2403 mg/day [the maximum dose] or <2403 mg/day). Patients, physicians, study staff and the sponsor were masked to treatment group allocation. The primary endpoint was assessment of adverse events, which were collected at each visit and for 28 days after the last dose of study drug. Exploratory efficacy measurements included forced vital capacity (FVC), carbon monoxide diffusing capacity, and 6 min walk distance. Analyses were done in the modified intention-to-treat population, which included all patients who were randomised and received at least one dose of study medication. This study is registered with the European Clinical Trials Database (EudraCT number 2012-000564-14) and has been completed. - Findings - 123 patients participated in the study between June 28, 2013, and Feb 24, 2015. 61 were assigned to the acetylcysteine group (60 received study medication and included in analysis) and 62 were assigned to the placebo group (all included in analysis). The occurrence of at least one adverse event (46 [77%] patients receiving acetylcysteine vs 50 [81%] receiving placebo), adverse events related to study treatment (17 [28%] vs 16 [26%]), and the number of patients experiencing severe adverse events (three [5%] vs two [3%]), life-threatening adverse events (one [2%] vs one [2%]), or death (one [2%] vs three [5%]) was similar between treatment groups. One case of diarrhoea in the acetylcysteine group was considered severe and related to study treatment. Nine serious adverse events were reported by seven patients: dyspnoea, headache, hypertension, intervertebral disc protrusion, and malignant lung neoplasm in the acetylcysteine group, and aortic aneurysm, contusion, forearm fracture, and worsening IPF in the placebo group. The most common adverse events were cough, nasopharyngitis, and diarrhoea. Photosensitivity occurred more frequently with acetylcysteine (eight [13%] patients) than placebo (one [2%] patient; difference 11·7%; 95% CI 2·6-20·9; p=0·016]), and was not attributable to differences in location, season, or concomitant medication. Four (7%) patients receiving acetylcysteine and three (5%) receiving placebo discontinued study treatment due to adverse events. In the exploratory analysis, change in FVC indicated that clinical benefit from addition of acetylcysteine to pirfenidone is unlikely, with the possibility of a harmful effect in patients with IPF (adjusted rate of decline 125·6 mL/6 months for acetylcysteine vs 34·3 mL/6 months for placebo; difference −91·3 mL; 95% CI −174·4 to −8·3; p=0·031). - Interpretation - Findings from the PANORAMA study suggest that addition of acetylcysteine to pirfenidone does not substantially alter the tolerability profile of pirfenidone, and is unlikely to be beneficial in IPF. - Funding - InterMune International AG (Roche).